Hypothesis: Clues From Mammalian Hibernation for Treating Patients With Anorexia Nervosa - Scolnick, Barbara (Frontiers in Psychology, 2018)
This hypothesis is that anorexia nervosa is a biologically driven disorder, and mammalian hibernation may offer clues to its pathogenesis. Using this approach, this hypothesis offers suggestions for employing heart rate variability as an early diagnostic test for anorexia nervosa; employing the ketogenic diet for refeeding patients, attending to omega 3:6 ratio of polyunsaturated fatty acids in the refeeding diet; and exploring clinical trials of the endocannabinoid-like agent, palmitoylethanolamde for patients with anorexia nervosa. This hypothesis also explores the role of lipids and autoimmune phenomena in anorexia nervosa, and suggest a lipodomics study to search for antibodies in the serum on patients with anorexia nervosa.